Perception, attitude and stigma of community pharmacists toward patients with mental disorders: a cross-sectional study: 10.55131/jphd/2024/220116 - Febrinasari, Nisa; Widayanti, Anna Wahyuni; Prabandari, Yayi Suryo; Satibi, Satibi (Journal of Public Health and Development, 2024)
One of the potential barriers to providing pharmaceutical care services to patients with mental disorders is stigma. Therefore, this study aims to explore the perception, attitude and stigma of community pharmacists toward patients with mental disorders in Indonesia. A self-report questionnaire was used including a convenience sample of 1,878 Indonesian community pharmacists from January to March 2023. The regression analyses showed that the perception in confidence level was significantly affected by age (95% CL :0.468-0.851; p-value:0.003) and work experience (95% CL: 1.205-2.284; p-value :0.002). Furthermore, age also affected the attitude of the community pharmacists towards patients with mental disorders (95% CL: 0.705-0.985; p-value: 0.033). Gender and a history of mental illness in a family member or a close friend contributed significantly to social distance (95% CL: 0.584-0.937; p-value: 0.013 and 95% CL: 1.212-1.779; p-value: <0.001, respectively). However, the self-disclosure of pharmacists about mental disorders remained unfavourable. In conclusion, this study found that majority of respondents had good perception and a low level of stigma towards patients with mental disorders. Based on the results, the continuous promotion of mental health awareness and education is recommended. In addition, sharing the personal experiences of individuals with mental disorders is essential for reducing self-stigma. Further studies are required to support service development in this field.